Relationship between Brand Personality and cognitive dissonance - Hana J Mohammed Al Askary, Atheer Abdulamer Al Mashady,; Mahdi Hasan, Huda (Opción, 2019)
The current research is intended disclosure to investigate the relationship and influence between the Brand Personality and cognitive dissonance via descriptive and analytical method. As a result, the personality of the brand relationships (correlation, effect) has a positive statistical function with the variables of cognitive dissonance combined. From the main conclusions of research are the responses of the research sample varied to the variable of brand sincerity by the sense of joy when dealing with that brand in addition to the benefit of its use.